2022
DOI: 10.3390/ijms23116330
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Permeation of Plasma-Generated Species from Vacuum into Water Bulk

Abstract: Due to their potential benefits, cold atmospheric plasmas (CAPs), as biotechnological tools, have been used for various purposes, especially in medical and agricultural applications. The main effect of CAP is associated with reactive oxygen and nitrogen species (RONS). In order to deliver these RONS to the target, direct or indirect treatment approaches have been employed. The indirect method is put into practice via plasma-activated water (PAW). Despite many studies being available in the field, the permeatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…A previous study also reported shorter streptococcal chains of S. mutans after CAP treatment compared with the pre-treatment length [11]. During plasma production, oxidants like hydrogen peroxide (H 2 O 2 ) accumulate at the vacuum-water boundary and within the water itself [40], implying that oxidants can infiltrate liquids. Thus, the RONS generated by CAP may reach the biofilm, potentially undermining the structural integrity of EPSs and leading to cell damage [41].…”
Section: Discussionmentioning
confidence: 94%
“…A previous study also reported shorter streptococcal chains of S. mutans after CAP treatment compared with the pre-treatment length [11]. During plasma production, oxidants like hydrogen peroxide (H 2 O 2 ) accumulate at the vacuum-water boundary and within the water itself [40], implying that oxidants can infiltrate liquids. Thus, the RONS generated by CAP may reach the biofilm, potentially undermining the structural integrity of EPSs and leading to cell damage [41].…”
Section: Discussionmentioning
confidence: 94%
“…Although this previous study did not explicitly examine biofilms, the shared characteristics of peptide and EPS aggregation suggest that the oxidizing effects of CAP may impede EPS cohesiveness within biofilm structures. Additionally, based on the reported concentrations of oxidizing agents, such as H 2 O 2 at the vacuum-water interface and within the water bulk during plasma generation [41], plasma-generated substances can permeate into liquids. These findings suggest that the reactive oxygen species (ROS) produced by CAP can be delivered to biofilms, potentially destabilizing EPS structure and causing cellular destruction [42].…”
Section: Discussionmentioning
confidence: 99%
“…The generated during CAP treatment initially interact with the water on the cell surface, before affecting the cell membrane [20]. Subsequently, RONS penetrate into the cell, inducing oxidative stress in the membrane, thereby forming lipid peroxide as the primary oxidation product and aldehyde, alcohol, and ketone as secondary products [21][22][23].…”
Section: Introductionmentioning
confidence: 99%